Driver's car following headway on single carriageway roads - Che Puan, Othman; Hainin, Mohd. Rosli; Chik, Abdul Aziz; Ismail, Che Ros (Faculty of Civil Engineering, 2002)
This report describes research to investigate drivers' behaviour on rural single carriageway roads. The study was carried out with the scope aiming at deriving the distance separation between impeded vehicles on single carriageway roads. Empirical models were developed to describe the driver's car-following distance at various operating speeds. Data defining headway and speed for more than 8000 vehicles were collected, using video cameras to record traffic movement at 4 sites in Malaysia. The video cassettes containing the traffic scenes were played-back in laboratory and data were extracted using a computer event recorder. All data were filtered to provide data and information for impeded only. The distance headways and associated vehicle speeds were separated into vehicle following category by vehicle type and then into speeds classes for vehicle following vehicle, car following car, car following HGV, HGV following HGV and HGV following car categories. In most cases the lognormal distribution was found to be an appropriate representation of the variation in distance headways for vehicles within a particular speed class. Linear regression models were developed to represent the relationships between distance headway and speed and hence to represent the predicted variation in population mean distance headway with vehicle speed. The results were compared with those from other studies, and the possible implications for single carriageway road traffic operational analysis were considered. In general, the results of the study provide evidence that most Malaysian drives tend to follow another vehicle closely on single carriageway roads. Platoons appeared to develop rapidly. Such information gathered from the study is useful for traffic engineers and planners in addressing traffic safety issues and traffic operational analysis.